LEGAL STABILITY OF THE STATE STATUS IN THE CONDITIONS OF THE GLOBALIZATION CRISIS: REVIEW OF THE BOOK «CRIMINAL LEGAL GUARANTEES OF SOVEREIGNTY STATES (COMPARATIVE LEGAL STUDY)» - Stanislav O. Gavrilov; Petr Y. Naumov (Russian Studies in Law and Politics)
Law, as a civilized form of regulation of social and international relations, among other things, must provide stable guarantees to subjects of legal relations to protect their status and that in the event of an illegal invasion of these rights, laws and international treaties will provide victims with an appropriate mechanism of legal protection, and vi- the new ones will be guaranteed fair and inevitable punishment. The objectives of scientific developments in the field of legal guarantees to states, as subjects of legal relations, are to summarize existing knowledge in this area and develop reasonable proposals for improving international legal mechanisms for the protection of rights. In 2023, at the Institute of Legislation and Comparative Law under the Government of the Russian Federation, an experienced scientific team, based on the application of the method of systemic and comparative legal research, generalized knowledge in the field of criminal legal guarantees of state sovereignty. Based on the research carried out, «the Prospekt» publishing house published a scientific and practical manual «Criminal legal guarantees of state sovereignty (comparative legal research)» under the responsible editorship of experienced legal scholars I.I. Kucherova, S.L. Nudel and O.I. Semykina. The team of authors united both experienced scientists recognized by the scientific community and representatives of the new generation of researchers of state legal and international legal sciences. This article reviews the named scientific and practical manual, highlights the starting points of the generalizations made, notes the positive aspects of the publication and issues that remained debatable after reading it. It is noted that the published scientific and practical manual is a convenient and useful tool for carrying out research, educational and educational activities.